"Girls Don't Propose! Ew.": A Mixed-Methods Examination of Marriage Tradition Preferences and Benevolent Sexism in Emerging Adults. (January 2013) - Robnett, Rachael D.; Leaper, Campbell
Thematic analysis was used to explore how emerging adults explained their preferences for two marriage traditions: marriage proposals and surname changes. Quantitative analyses were subsequently used to examine the association between benevolent sexism and participants' marriage-tradition preferences. A sample of 277 undergraduates ( M = 19 years) completed a survey that included open- and closed-ended questions about attitudes toward marriage traditions and gender-role ideology. Results of the thematic analysis indicated that both women and men tended to hold traditional marriage preferences—especially with regards to marriage proposals. Multiple regression indicated that endorsing benevolent sexism was related to holding more traditional preferences. The findings are interpreted in relation to the role that hidden power may play in many heterosexual romantic relationships.